Pengaruh Metode Pembiasaan dalam Melatih Kemandirian Anak Usia Dini di TK Nurul Hikmah NW Pepao NTB - Suhaini, Suhaini (YASIN, 2023)
The background of this research is that the independence of children aged 4-5 years is still low because of the teacher's lack of attention to the independence of children aged 4-5 years and the habits that are applied by the teacher are not consistent. The purpose of this study was to determine the independence of children aged 4-5 years, before and after the habituation method was applied and to determine the effect of the habituation method on children's independence. This research was conducted at Kindergarten Nurul Hikmah NW Pepao NTB, with a total of 25 children using the habituation method. The method used in this study is an experimental method with a one-group pretest-posttest pre-experimental design. Data collection techniques are through observation, and documentation. Data analysis was performed by normality test and hypothesis testing. The results of the pretest before the habituation method was applied were said to be still low, this was evidenced by the Kolmogorov Smirnov score of 0.196 > 0.05 which indicated that the independence of children aged 4-5 years was still relatively low in the three characteristics of independence found, namely having self-confidence, being responsible responsibility, and not depend on others. Posttest results after the habituation method was applied, the independence of children aged 4-5 years had increased with a Kolmogorov Smirnov value of 0.745 > 0.05 which indicated that the independence of children aged 4-5 years had increased in the three characteristics of children's independence, namely having self-confidence, responsible, and not depend on others. The results of the influence of the habituation method in training the independence of children aged 4-5 years can be seen from the habituation method coefficient value of 0.785 and a significant value of 0.021. While the results of the F hypothesis test are 6.136 > 3.39 the calculated F value is greater than the table F value. The coefficient of determination ( ) is 21%. From the results of these data it can be concluded that the habituation method has a positive and significant effect in training the independence of children aged 4-5 years in Kindergarten Nurul Hikmah NW Pepao NTB.